Vitamin D receptor gene FokI polymorphisms influence bone mass in adolescent football (soccer) players - Diogenes, M. E. L.; Bezerra, F. F.; Cabello, G. M. K.; Cabello, P. H.; Mendonca, L. M. C. (European Journal of Applied Physiology, 2010)
The genetic influence on bone mineralization during adolescence is unclear possibly due to modifying factors such as skeletal maturation and lifestyle. We evaluated the influence of polymorphisms of the vitamin D receptor (VDR) gene on longitudinal changes in bone mass, bone- and calcium-related hormones in 46 adolescent soccer players (11.8-14.2 years). Total body bone mineral content (TBMC) and density (TBMD) were measured at baseline and after 6 months. Insulin-like growth factor-I (IGF-1), testosterone, intact parathyroid hormone, and activity of plasma bone alkaline phosphatase were measured at baseline and after 3 months. The influence of FokI or TaqI VDR genotypes on changes in the outcome variables were analyzed by univariate ANOVA with adjustment for chronological age, skeletal age and body weight at baseline. At baseline, boys with Ff genotype had higher TBMC, TBMD, TBMD Z-score compared to those with FF genotype (P < 0.05). After 3 months, Ff boys also had higher increment in plasma IGF-1 (P < 0.05). FokI polymorphism did not influence changes in bone mass measurements after 6 months, although differences detected at baseline remained significant after 6 months. There were no differences in the outcome variables according to TaqI genotypes. This study demonstrates that FokI polymorphisms affect bone mass in Brazilian adolescent soccer players and suggests that the FokI effect on bone mineralization occurs during bone maturation, possibly at the initial pubertal stages.